AVALIAÇÃO CLÍNICA DO USO PRÉ-OPERATÓRIO DA DEXAMETASONA E IBUPROFENO PARA CONTROLE DA DOR NO TRATAMENTO ORTODÔNTICO - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2012)
The pain may be the main reason of interruption ordiscontinuance of orthodontic treatment. Most patients experience at some stage of the treatment any kind of pain anddiscomfort. The aim of this randomized double-blind parallel placebo- ontrolled clinical trial was to compare the clinical actionof the preemptive use of dexamethasone and ibuprofen for reliefor pain control during orthodontic treatment. It was selected one hundred patients in orthodontic treatment in the clinic of orthodontics at State University of Ponta Grossa. The mean age was 25 years (range from 18 to 49 years). Patients were divided into three experimental groups: G1 (n = 25) received anenvelope containing 600mg of ibuprofen arginine 555mg withG2 (n = 25) one tablet of 4mg dexamethasone; G3 (n = 50) placebo control. Each participant answered a questionnaire inwhich dental anxiety reported prior experience with the treatmentof pain. The drugs were administered previously the query of placing rectangular arches, and each participant wrote downspecific form of the experience of pain at times 2,6,12,24 and 48hours after device activation. To measure the pain experience of each participant was used a numerical scale of 101 points(NRS).The results showed that except in time of 2 hours, G1 and G3 showed no statistically significant differences . The G2 group showed the lowest pain scores at all times and showed statistically significant differences compared to G1 and G3. It may be concluded that ibuprofen is effective for pain relief only in a period of up to 2 hours after orthodontic activation and that dexamethasone may be indicated as a medication of choice because it is efficient in the period up to 48 hours.
Germiniani, WIS. Clinical evaluation of the preemptive use of dexamethasone and ibuprofen for pain control in orthodontic treatment
Keywords: dor; anti-inflamatórios; movimentação ortodôntica; pain; antiinflammatories; orthodontic movement; CNPQ::CIENCIAS DA SAUDE::ODONTOLOGIA